Antimutagenicity and DT-diaphorase inducing activity of Gynostemma pentaphyllum Makino extract - Kulwat C. (2014)
The hot water extract of the herbal tea, Gynostemma pentaphyllum Makino, was not found to be mutagenic in Salmonella mutation assay with or without metabolic activation. However, the extract had both DT-diaphorase inducing activity in the murine hepatoma (Hepa1c1c7) cell line and antimutagenic properties towards chemical-induced mutation in Salmonella typhimurium strains TA98 and TA1OO. Mutagenicity of aflatoxinB1 (AFB1),2-amino-6- methyldipyrido [1,2-a:3',2',3-d] imidazole (Glu-P-1), 2-aminodipyrido [1,2-a:3',2',3-d] imidazole (Glu-P-2), 2-amino-1, 4-dimethyl-5H-pyrido [4,3-b] indole (Trp-P-1), 3-amino-1-methyl-5H-pyrido [4,3-b] indole (Trp-P-2), 2-amino-3-methylimidazo [4,5-f] quinoline (IQ) and Benzo [a] pyrene (B[a]P) was inhibited by the extract of Gynostemma pentaphyllum Makino in a dose-dependent manner, but no effect was found on the mutagenic activity of 2-(2-Furyl)-3-(5-nitro-2-furyl) acrylamide (AF-2). However, the extract enhanced the mutagenicity induced by 2-aminoanthracene (2AA), and N-methyl-N'-nitro-N- nitrosoguanidine (MNNG).